2018
DOI: 10.4038/jccpsl.v24i2.8149
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitudes on unsafe abortions among the state university undergraduates in Western Province

Abstract: Background: Abortion is legally permitted in Sri Lanka only to save mother's life. A great majority of undergraduates reside away from home and are vulnerable to risky behaviour. However, their knowledge and attitudes on abortion are scarce in Sri Lanka. Objective: To describe the knowledge and attitudes on unsafe abortions among undergraduates in the state universities of Western Province, Sri Lanka Methods: A descriptive cross-sectional study was conducted among 1575 second and third year undergraduates usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…This result is similar to other studies done in Port Harcourt (Nigeria), Sri Lanka and Ethiopia which documented that majority of women who procure abortion were usually young and unmarried, also, these studies were done among secondary and university students. 10,14,15 This corroborates the fact that the adolescent and early adults are the major age group at risk of induced abortion. The world health organization has also revealed that the age group 15-24 years in African region accounted for more than 50% of the global abortion-related mortalities.…”
Section: Discussionsupporting
confidence: 65%
“…This result is similar to other studies done in Port Harcourt (Nigeria), Sri Lanka and Ethiopia which documented that majority of women who procure abortion were usually young and unmarried, also, these studies were done among secondary and university students. 10,14,15 This corroborates the fact that the adolescent and early adults are the major age group at risk of induced abortion. The world health organization has also revealed that the age group 15-24 years in African region accounted for more than 50% of the global abortion-related mortalities.…”
Section: Discussionsupporting
confidence: 65%
“…Different factors have been identified as being associated with SRBs among undergraduates from research conducted during the past decades. Socio-economic and demographic factors, personality, self-esteem, health and knowledge and presence of other health risk behaviors such as risky substance use, family and parental factors, adverse childhood events, and school and peer-related factors were significantly associated with SRBs (Bori and Jelena 2015;Caspi et.al., 1997;Espelage, Basile, & Hamburger, 2012;Khalaj, Abadi, John, and Amir, 2011;Kebede, et.al., 2005;Perera, and Abeysena, 2018a;Perera, and Abeysena, 2018b;Ramiro, Madrid & Brown, 2010;Ssewanyan, 2018;Yi, Te, Pengpid, & Peltzer, 2018). Furthermore, Institutional/university-related factors included academic performance, living in hostels, going to parties, presence of a roommate and peer delinquency behavior and societal factors like discrimination faced by undergraduates have been assessed for association with SRBs among undergraduates (Chanakira, O'Cathain, Goyder, & Freeman;2014;Gardner, & Steinberg, 2005;Piña-Watson, Cox, & Neduvelil, 2021).…”
Section: Introductionmentioning
confidence: 99%